2008
DOI: 10.1248/jhs.54.324
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Anion Adsorption and Physicochemical Properties of Aluminum Oxide

Abstract: This study investigated the adsorption capacity and adsorption mechanism of phosphate by calcined aluminum oxide (GB) at temperatures of 200 to 1150• C. The results showed that GB and GB calcined at a temperature of 200• C exhibited almost no adsorption capacity, and GB calcined at temperatures of 300 or 400• C exhibited the highest adsorption capacity. After that, adsorption capacity tended to decrease with increasing calcination temperature. The specific surface area and the concentration of surface hydroxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 15 publications
(12 reference statements)
0
25
0
1
Order By: Relevance
“…Previous reports have shown that the highest amount of phosphate adsorbed was obtained using calcined GB at 450 P-GB and virgin CE P-CE 18 . The phosphate adsorption isotherms of GB and CE are shown in Fig.…”
Section: Adsorption Isothermsmentioning
confidence: 82%
“…Previous reports have shown that the highest amount of phosphate adsorbed was obtained using calcined GB at 450 P-GB and virgin CE P-CE 18 . The phosphate adsorption isotherms of GB and CE are shown in Fig.…”
Section: Adsorption Isothermsmentioning
confidence: 82%
“…We have previously reported the amount of phosphate adsorbed based on specific surface area and surface hydroxyl groups. The amount of phosphate adsorbed onto GA was greater than that onto virgin BE, as the specific surface area of GA is larger (The adsorption capacity and specific surface area of GA or virgin BE is 74.2 mg/g and 283.1 m 2 /g or 56.9 mg/g and 253.9 m 2 /g, respectively) (Kabayama et al, 2005;Kawasaki et al, 2008). The experimental data were fitted to the Langmuir and Freundlich isotherm equations.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum adsorption of phosphate occurs at a pH of about 3. Kawasaki et al (2008) reported that the adsorption mechanism for phosphate ions onto aluminum compounds was by ion exchange with surface hydroxyl groups on the aluminum compounds. In this study, we used GA as the adsorbent for the removal of phosphate.…”
Section: Effect Of Solution Ph On Phosphate Adsorption Onto Gamentioning
confidence: 99%
“…A previous study reported similar trends. 21) We also evaluated the amount of phosphorus on the GB400 surface (Fig. 3).…”
Section: -23)mentioning
confidence: 99%
“…Kawasaki et al reported that the optimal pH for adsorption of orthophosphoric acid on aluminum oxide at different temperatures was acidic (pH around 4.0). 21) Many researchers have reported that the adsorption of condensed phosphates improved with decreasing pH. 24) The increase in the amount of condensed phosphates adsorbed on aluminum hydroxide at low pH could be attributed to electrostatic attraction and acid catalysis, as illustrated by the follow- Effect of Contact Time on Phosphoric Acid Adsorption on GB400 Figure 5 shows the adsorption rates of phosphoric acids on GB400; equilibrium was reached within 24 h. The amount adsorbed increased in the order orthophosphoric acid>pyrophosphoric acid>tripolyphosphoric acid.…”
Section: -23)mentioning
confidence: 99%